2019
DOI: 10.7771/2157-9288.1214
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Positional Identity in an Elementary Professional Learning Community: A Case Study

Abstract: Professional learning communities are typically conceived of as spaces for reducing teacher isolation, supporting informed and committed teachers, and fostering student academic gains. Focusing on a professional learning community that supported the teaching and learning of engineering in elementary schools, we also conceived of this learning environment as a space for negotiating a teacher-ofengineering identity. Calling attention to emergent issues of power and status through a lens of positional identity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Often teachers' professional learning opportunities centered on educational equity are considered separate from the disciplines (King & Butler, 2015). This article adds to a growing body of work emphasizing the need for educators to consider discipline‐specific perspectives in disrupting oppressive educational practices, systems, and structures (Gutiérrez, 2013; Larkin, 2019; Patterson & Gray, 2019; Wright et al, 2020). For instance, the finding that teachers can retool discourses of hierarchy using engineering‐specific skills suggests the need to reflect on how to disrupt status rankings without setting up new winners and losers.…”
Section: Discussionmentioning
confidence: 99%
“…Often teachers' professional learning opportunities centered on educational equity are considered separate from the disciplines (King & Butler, 2015). This article adds to a growing body of work emphasizing the need for educators to consider discipline‐specific perspectives in disrupting oppressive educational practices, systems, and structures (Gutiérrez, 2013; Larkin, 2019; Patterson & Gray, 2019; Wright et al, 2020). For instance, the finding that teachers can retool discourses of hierarchy using engineering‐specific skills suggests the need to reflect on how to disrupt status rankings without setting up new winners and losers.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this, the government's aim to become one of the top education centers in the southeast Asian area necessitates a number of adjustments in order to improve the quality of the country's education system [6]. As a result, hardworking school personnel display great levels of enthusiasm and a strong feeling of love for school by demonstrating high dedication at all times without expecting rewards in order to witness their kids' achievement [7]. In reality, administrators' practice and leadership qualities were discovered to be able to impact teacher motivation [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bektaş, Kılınç, and Gümüş [16] showed that professional learning communities may not only improve the quality of instructors' education but also provide teachers the freedom to make decisions and foster social connections among students. Indeed, professional learning communities may bridge the gap between leaders and teachers, minimize teacher isolation, and give encouragement and support among dedicated school personnel in order to enhance student accomplishment with excellence [7]. Furthermore, professional learning communities have been identified as a small collaborative team that needs each other, works together, enables effective learning, and provides opportunities for collectively exchanging ideas, reflecting on, and sharing knowledge for the sake of educational sustainability [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we explore how aspirational capital functioned to support the teachers' perceptions of self along their engineering pathways, as well as how, as Black teachers in a predominantly Black school, they intentionally offer their students counternarratives (Solórzano & Yosso, 2002) of who engineers can be. We contend that this research is of particular importance because despite an emerging body of literature focused on the engineering experiences of students from historically marginalized communities (Burt et al, 2019;Gibson & Espino, 2016;McGee & Martin, 2011;Moore, 2006;Samuelson & Litzler, 2016;Wright et al, 2018), there remains a gap in knowledge specifically addressing the educational and professional experiences of Black women teachers of engineering (Wright et al, 2020) and their potential role as change agents in k-12 engineering spaces (Wallace et al, 2014).…”
Section: Introductionmentioning
confidence: 99%